2018
DOI: 10.23736/s0026-4784.18.04296-x
|View full text |Cite
|
Sign up to set email alerts
|

Findings from the Italian Babies Born Better Survey

Abstract: BacKGroUND: The most recent WHo recommendations "intrapartum care for a positive childbirth experience" highlight the need to identify women-centered interventions and outcomes for intrapartum care, and to include service users' experiences and qualitative research into the assessment of maternity care. Babies Born Better (B3) is a trans-european survey designed to capture service user views and experiences of maternity care provision. italian service users contributed to the survey. MeTHoDS: The B3 Survey is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 12 publications
(10 reference statements)
2
22
0
Order By: Relevance
“…Therefore, it is possible that women would have reported more positive feelings prior to the commencement of the pandemic. Understandably, this was not possible due to the unexpected nature of the pandemic and it is important to note that the feelings reported by women in the present study, in reference to ‘normal’ conditions, are consistent to what has been previously reported in interviews with Italian women [ 37 ].…”
Section: Study Limitationssupporting
confidence: 88%
“…Therefore, it is possible that women would have reported more positive feelings prior to the commencement of the pandemic. Understandably, this was not possible due to the unexpected nature of the pandemic and it is important to note that the feelings reported by women in the present study, in reference to ‘normal’ conditions, are consistent to what has been previously reported in interviews with Italian women [ 37 ].…”
Section: Study Limitationssupporting
confidence: 88%
“…Most of mothers provided more than one inputs and requests for improving the QMNC. This is the first study in Italy documenting views of women, after giving birth in a hospital, on how to improve the QMNC: we were able to identify three previous research reporting on the women's experience of care during childbirth in Italy, but these did not include practical suggestions, as expressed by women, on how to improve it [25,29,30]. Additionally, this is the first study utilising the WHO Standards [19] as framework for the thematic analysis on women's suggestions on how to improve the QMNC, and may serve as model for future research.…”
Section: Discussionmentioning
confidence: 99%
“…We acknowledge that this study was conducted in one single facility in Italy, and as such findings are not generalizable to other Italian hospitals. Previous studies reported clear differences in practices (such as caesarean section rate) as well as in the experience of care among different geographical regions in Italy, and even among nearby facilities in the same region [6,29]. For example, it is possible that the maternal and newborn outcomes influenced indirectly the perception of the QMNC with Halo effect, ie, the behavior, usually unconscious, of using evaluations based on things unrelated, to make judgments about something or someone [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…10 There are a number of parallel movements happening in maternity care in italy, including the creation of birth centers, and the evidence from some sites of positive collaboration between women, midwives, obstetricians, and others working in maternity care. as Skoko et al have noted in their article published in the present issue of Minerva Ginecologica, 11 there is evidence of good practice around italy from the italian Babies Born Better survey of the views of women who have children under the age of 5. in recognition of the global move towards the need for health services to promote thriving, the authors note that there are areas…”
mentioning
confidence: 68%
“…italy has one of the highest caesarean section rates in europe, second only to cyprus. 14 Some of the issues underneath this statistic are also explored by Skoko et al 11 in addition, they are picked up by Hadjigeorgiou et al 15 who examine the way the media report on matters relating to maternity care in both italy and cyprus. They contrast these findings with the approach of the media in iceland, which has one of the lowest caesarean section rates in the world, 14 as well as one of the lowest perinatal mortality rates.…”
mentioning
confidence: 99%